REMARK ON SOME RISK FACTORS AND ACCOMPANIED INJURIES IN VICTIMS SUBARACHNOID HEMORRHAGE THROUGH THE FORENSIC EXAMINATION OF REMAINS - Dao Hoang Diem,; Nguyen Duc Nhu,; Luu Sy Hung,; Luu Thanh Thuy,; Pham Hong Thao, (Tạp chí Y học Quân sự, 2023)
Remark on some risk factors and accompanying injuries in patients with subarachnoid hemorrhage. Subjects and methods: A retrospective descriptive study on 93 forensic examination records of victims who died caused by subarachnoid hemorrhagic injuries at the Department of Pathological anatomy-Forensic Medicine, Viet Duc Friendship Hospital, and some Centers of Forensic medicine from January 2007 to December 2017. Results: The risk factors: men (81.7%) suffered from subarachnoid hemorrhage more than women (18.3%). The average age of the victims was 37 years, of which the most common victims were 15-29 years old (43.0%). The majority of victims with subarachnoid hemorrhage were due to traffic accidents (66.7%). 33/46 of victims (71.7%) tested with alcohol concentration in blood. The subarachnoid hemorrhage and accompanied injuries: the most common scalp injury was subcutaneous hematoma (91.4%). The rate of victims with skull fractures was high (75.3%). The most common intracranial injury was cerebral contusion (54.8%). Histopathology: the most common injury was cerebral edema (69.8%), followed by atherosclerosis (23.3%) and aneurysm malformation (9.35%).